Numerical prototyping of lateral flow biosensors - Schaumburg, Federico (2018)
Lateral flow biosensors (LFB) have become a hot topic in the scientific literature in association with the rapid growing of paper-based microfluidics. Improving the existing LFB technology is a challenging task that demands large experimental efforts. Thus computer simulations are practical tools to assist the development of novel devices, since running virtual experiments considerably reduces costs and time in the path from design to real LFB prototypes. We present a computational tool for 3D numerical prototyping of LFB, which accounts for the fluid dynamics (including capillary-driven flow) in the heterogeneous porous materials, the transport of reactive components, and all the biochemical reactions involved. Mathematical modeling was carried out in the framework of continuum transport phenomena, and numerical calculations were implemented by using the finite element method. This numerical prototyping allows developers to explore arbitrary architectures, materials, and assay formats, which is demonstrated here by discussing different real-world examples. The advantages of the proposed numerical model are also discussed in relation to up-to-date reported methods.